The economics of civil and common law - Madjd-Sadjadi, Zagros, 1968- (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Law is supposed to encourage innovation, morality, and conformity with societal expectations, yet it may provide perverse incentives causing individuals, or even the State, to act in discordant, inefficient, and even immoral ways. It will explore the inefficiencies that are created that serve to deny individuals work and shelter in a haphazard and capricious manner. It will examine property rights, including eminent domain that lets the State take property away with seemingly arbitrary compensation to the owner. Individuals must understand both civil law, codified by statutes, and common law, enshrined in precedential judicial decisions, and why the common law tends to better reduce transactions costs and thus avoid courts entirely. This book is written for economists and noneconomists and has an extensive glossary of economic, political, and legal terms. Two items that are not formally treated in other economics of law textbooks are the legal organization of businesses and tax law from an economics perspective.
1. The interaction of law and economics -- 2. Property rights -- 3. Contracts -- 4. Torts -- 5. Organization of the firm and competition law -- 6. Other laws -- Glossary -- Notes -- References -- Index.
Includes bibliographical references (pages 187-194) and index.
Title from PDF title page (viewed on November 30, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Law and economics; Law -- Economic aspects; adverse selection; antitrust law; civil law; climate change; Coase theorem; common law; contracts; corporate personhood; deadweight loss; discrimination; externalities; family law; free trade; information asymmetry; Laffer curve; moral hazard; patents; Pigouvian tax; precedent; price discrimination; principal-agent program; property rights; Supreme Court decisions; tax incidence; Theory of the Firm; torts; transaction costs; unconscionability; Electronic books